Implementing and developing cloud computing applications - Sarna, David E. Y. (Boca Raton : CRC Press, 2011)
"Major enterprises and small start-ups are beginning to embrace cloud computing for the scalability and reliability that cloud vendors can provide. This book demonstrates how to implement robust and highly scalable cloud computing applications. Filled with comparative charts and decision trees to help navigate the many implementation alternatives, the author describes the major available commercial offerings and guides readers in choosing the best combination of platform, tools, and services for a small, growing start-up or an established enterprise. Aimed at software developers and their managers, the text details cloud development environments, lifecycles, and project management"--
ch. 1. Cloud computing is a true paradigm shift -- ch. 2. From do it yourself to public cloud : a continuum -- ch. 3. Cloud computing : is it old mainframe Bess in a new dress? -- ch. 4. Moving into and around the clouds and efforts at standardization -- ch. 5. Cloud economics and capacity management -- ch. 6. Demystifying the cloud : a case study using Amazon's cloud services (AWS) -- ch. 7. Virtualization : open source and VMware -- ch. 8. Securing the cloud : reliability, availability, and security -- ch. 9. Scale and reuse : standing on the shoulders of giants -- ch. 10. Windows Azure -- ch. 11. Google in the cloud -- ch. 12. Enterprise cloud vendors -- ch. 13. Cloud service providers -- ch. 14. Practice fusion case study -- ch. 15. Support and reference materials.
"An Auerbach book."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cloud computing; Business -- Data processing; Electronic books